Faith Education in Islamic Education - Andri Kusnandar; Iskandar Mirza (Classroom: Journal of Islamic Education, 2025)
Faith education is the instillation of faith and divine values by someone who has more religious experience and has weak faith qualities in order to become stronger. The importance of faith education requires teaching the faith exemplified by Luqman to be imitated by all parents and educators. Parents and educators have an obligation to foster a comprehensive understanding of the faith and teachings of Islam from the beginning of its growth, so that children will be bound by Islam, both aqidah and worship. And with this faith education, it is hoped that children will only know Islam as their religion, the Qur'an as their Imam and Rasulullah SAW as their leader and example. Things that destroy faith are shirk, namely equating other than Allah with Allah in things that are His privilege and riddah means leaving the teachings of Islam, the perpetrator is called an apostate. Every Muslim is obliged to protect his Islam and protect it from things that damage, cancel and break his Islam. Mufasir's views on faith education contained in QS. Luqman verse 13 tells the story of Luqman al-Hakim, a wise father, who really emphasized the importance of instilling monotheism in his children. Zakiyah Drajat emphasized that building strong faith should start in the family, from the time the child is born and even before birth until the end of adolescence. If childhood neglects education, it will be difficult for children to face changes in themselves, as a result it often brings emotional shock.